Consumer and carer leadership in palliative care academia and practice: A systematic review with narrative synthesis. (September 2019) - Scholz, Brett; Bevan, Alan; Georgousopoulou, Ekavi; Collier, Aileen; Mitchell, Imogen
Background: Contemporary health policies call for consumers to be part of all aspects of service planning, implementation, delivery and evaluation. The extent to which consumers are part of the systemic decision-making levels of palliative care appears to vary between and within services and organisations. Aim: The aim of this systematic review is to develop understandings about consumer and carer leadership in palliative care. Design: A systematic, narrative synthesis approach was adopted due to the heterogeneity of included studies. The review was registered on PROSPERO prospectively (PROSPERO 2018 CRD42018111625). Data sources: PubMed, Scopus and PsycINFO were searched for all studies published in English specifically focusing on consumers' leadership in palliative care organisations and systems. Articles were appraised for quality using a modified JBI-QARI tool. Results: Eleven studies met the inclusion criteria and quality assessment. Consumers are currently involved in leadership of palliative care teaching, research and services. Findings highlight the benefits of consumer leadership in palliative care including more relevant, higher-quality services, teaching and research. Across the included studies, it was not clear the extent to which consumer leaders had influence in relation to setting agendas across the palliative care sector. Conclusion: The findings suggest that more could be done to support consumer leadership within palliative care. Academics and clinicians might improve the relevance of their work if they are able to more meaningfully partner with consumers in systemic roles in palliative care.